2019
DOI: 10.1002/lsm.23126
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Fractional CO2 Laser Treatment on the Symptoms of Pelvic Floor Dysfunctions: Pelvic Floor Distress Inventory‐20 Questionnaire

Abstract: Background and Objectives To assess the improvement on pelvic floor distress (PFD)‐related urogenital symptoms using validated questionnaires after intravaginal CO2 laser treatment. Study Design/Materials and Methods Forty postmenopausal women with genitourinary symptoms of menopause (GSM) were enrolled into this prospective cohort study and underwent vaginal laser treatment using MonaLisa Touch® fractional CO 2 laser system. Patients received three vaginal laser treatments with 360° probe 4 weeks apart. A thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 32 publications
2
19
0
Order By: Relevance
“…This study showed that the positive effects of laser treatment on vaginal laxity and sexual function waned by 6 months. A significant subjective improvement and the partial objective improvements observed at 3 months after 3 treatment sessions, and the decline during the subsequent 3 months post‐treatment collaborate the results of previous case series [14–36]. The objective parameter assessed (VHI) declined to pre‐treatment baseline levels at 6 months, while subjective parameters (FSFI and monthly sexual intercourse rate) demonstrated a slower, though significant decline at 6 months.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…This study showed that the positive effects of laser treatment on vaginal laxity and sexual function waned by 6 months. A significant subjective improvement and the partial objective improvements observed at 3 months after 3 treatment sessions, and the decline during the subsequent 3 months post‐treatment collaborate the results of previous case series [14–36]. The objective parameter assessed (VHI) declined to pre‐treatment baseline levels at 6 months, while subjective parameters (FSFI and monthly sexual intercourse rate) demonstrated a slower, though significant decline at 6 months.…”
Section: Discussionsupporting
confidence: 85%
“…All tests were considered significant at the 0.05 level. The sample size was based on previous studies that showed a statistically significant change following laser treatment [15–36].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most recently vaginal laser treatment was introduced as a new option for women with GSM and vaginal dryness. Several clinical studies have investigated the efficacy and revealed the beneficial effects of vaginal laser treatment . Currently, there are promising data regarding improvement in subjective symptoms of GSM, vaginal health and flora, sexual function and dyspareunia, and urinary incontinence .…”
Section: Introductionmentioning
confidence: 99%
“…Several clinical studies have investigated the efficacy and revealed the beneficial effects of vaginal laser treatment . Currently, there are promising data regarding improvement in subjective symptoms of GSM, vaginal health and flora, sexual function and dyspareunia, and urinary incontinence . Prior publications revealed that vaginal cytology had improved significantly, reflected by an increase in the vaginal maturation values (VMV) after vaginal laser treatment in postmenopausal women with GSM .…”
Section: Introductionmentioning
confidence: 99%